2002
DOI: 10.1002/ajpa.10070
|View full text |Cite
|
Sign up to set email alerts
|

Are all grandmothers equal? A review and a preliminary test of the “grandmother hypothesis” in Tokugawa Japan

Abstract: An unresolved question arising from human evolutionary research relates to the function of the postreproductive period in human females. If menopause is not merely an artifact resulting from the benefits of civilization, there must be an adaptive mechanism favoring the offspring of women who continue to thrive well past the time of their last ovulation. The "grandmother hypothesis" was developed on the basis of the original suggestion by Williams (1957 Evolution 11:32-39) that "stopping early" would benefit al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 60 publications
4
81
0
Order By: Relevance
“…To date, only two previous studies known to the authors have distinguished between boys and girls when investigating the effect of both grandmothers. A study of a Japanese population found that the presence of a PGM had a negative effect on boys and a positive effect on girls, while the presence of an MGM had a positive effect on children of both sexes, especially on boys (Jamison et al 2002). They point to cultural features of the society as a possible mechanism for these findings.…”
Section: The Grandmother Hypothesismentioning
confidence: 98%
“…To date, only two previous studies known to the authors have distinguished between boys and girls when investigating the effect of both grandmothers. A study of a Japanese population found that the presence of a PGM had a negative effect on boys and a positive effect on girls, while the presence of an MGM had a positive effect on children of both sexes, especially on boys (Jamison et al 2002). They point to cultural features of the society as a possible mechanism for these findings.…”
Section: The Grandmother Hypothesismentioning
confidence: 98%
“…In pre-modern and traditional populations the presence of grandmothers are found to improve child survival rates (e.g. Jamison et al 2002;Ragsdale 2004;Lahdenperä et al 2004;Sear et al 2000;2003;Voland and Beise 2002), while grandfathers are found to have much less beneficial or even unbeneficial impact on child survival (e.g. Dong et al 2016;Lahdenperä et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It may, conversely, underestimate kin effects if after a death, other kin step in to provide necessary help. A popular alternative measure of kin availability is co-residence with kin, sometimes measured by postnuptial residence (see examples: Snopkowski and Sear 2013;Thornton et al 1986;Skinner 2004;Jamison et al 2002;Tsay and Chu 2005). This measure may be biased if individuals who live with kin after marriage are systematically different from those who do not.…”
Section: Introductionmentioning
confidence: 99%